Prevalence of congenital missing of maxillary laterals and mandibular second premolars in patients referred to Islamic Azad University, Dental Branch of Tehran, in a one-year period - Ramin Kaviani; Sayed Alireza Makkinejad; Fatemeh Heidari; Vahid Rakhshan (Isfahan University of Medical Sciences, 2012)
Introduction: Congenital missing of maxillary lateral and mandibular second premolar teeth is one of the most prevalent developmental anomalies. The aim of this study was to determine the prevalence and pattern of congenital missing of maxillary lateral and mandibular second premolar teeth in patients referred to the Department of Maxillofacial Radiology, Islamic Azad University, Dental Branch of Tehran, in 2009. Materials and Methods: In this descriptive cross-sectional study, 645 panoramic radiographs of 12-25 year-old patients (314 boys and 331 girls) were evaluated in relation to missing of maxillary lateral and mandibular second premolar teeth. Data were analyzed using chi-squared test (α = 0.05). Results: Among 645 panoramic radiographs, 56 cases were found to have missing teeth (8.7%). The prevalence of congenital missing of maxillary lateral incisors was higher than that of mandibular second premolars, with no statistically significant differences (p value = 0.17). There was no significant correlation between missing teeth and gender (p value = 0.94). No significant differences were seen in the prevalence of missing teeth between the right and left sides (p value = 1). Conclusion: This study showed a rather high prevalence of missing teeth in Iranian dental patients. Therefore, accurate and frequent examination of children is crucial for early diagnosis since missing can cause serious problems in esthetic and speech. Key words: Hypodontia, Permanent teeth, Prevalence